Interaksi di Media Sosial Instagram Terhadap Pembentukan Citra Diri Pada Mahasiswa UIN Sumut - Khairi, Faris Al; Lubis, Faizal Hamzah (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
Social media Instagram is generally used by students to interact and display their self-image. The purpose of this study is to explain the interaction on social media Instagram towards the formation of self-image in UIN Sumut students. The study was limited to only examining sixth-semester female students of UIN Sumut Faculty of Islamic Economics and Business, this is based on the researcher's assumption that female students generally take great care of their appearance on Instagram as part of their self-image. Data collection used questionnaires, literature reviews, scientific articles and documentation. The population was 709 female students with a sample of 92 female students. The study used a quantitative approach with a correlational method. The results of the research data processing obtained a correlation coefficient value of 0.9095. This value indicates a very strong and significant influence of interaction on Instagram on the formation of female students' self-image. The determination test showed that 82.7% of the formation of female students' self-image can be explained by their interactions on social media Instagram, the remaining 17.3% is explained by other factors.